2018
DOI: 10.1097/aln.0000000000002275
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Care Team Composition and Surgical Outcomes

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background In the United States, anesthesia care can be provided by an anesthesia care team consisting of nonphysician providers (nurse anesthetists and anesthesiologist assistants) working under the supervision of a physician anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…While Posner's findings suggested that in a large university program outcomes were not impacted by team composition, productivity, or concurrency, she acknowledged that the role of specific individuals was not studied. More recent work has supported these findings by reviewing a national claims database of 443,000 Medicare beneficiaries [13]. In this study, there were no significant differences observed between different care models and costs, length of stay, and/or mortality.…”
Section: Discussionsupporting
confidence: 67%
“…While Posner's findings suggested that in a large university program outcomes were not impacted by team composition, productivity, or concurrency, she acknowledged that the role of specific individuals was not studied. More recent work has supported these findings by reviewing a national claims database of 443,000 Medicare beneficiaries [13]. In this study, there were no significant differences observed between different care models and costs, length of stay, and/or mortality.…”
Section: Discussionsupporting
confidence: 67%
“…The influence on outcome of other factors, such as complexity of the interventional procedure or emergency intervention, will have to be investigated. 6,[18][19][20][21] In conclusion, results of the present retrospective study show that the risk of 30-day death and hospital LOS are substantially lower if an anaesthesia nurse is present and supervised by an anaesthesiologist, compared with a solo anaesthesiologist. The research shows an interesting association.…”
Section: Discussionmentioning
confidence: 89%
“…A common type of instrumental variable is called the hospital preference instrumental variable, which has been used in previous studies in perioperative medicine. 38 This approach assumes that the local practice pattern (in our case the proportion of hip fracture patients at each participant's hospital who received a peripheral nerve block Copyright © 2019, the American Society of Anesthesiologists, Inc. Unauthorized reproduction of this article is prohibited.…”
Section: Prespecified Sensitivity Analysesmentioning
confidence: 99%